Diseases of the adrenal gland and their heredity (Texas Journal of Medical Science, 2025)
This article provides a comprehensive analysis of the causes of pancreatic diseases, their forming factors, especially the role of hereditary factors. The genetic basis of diseases such as pancreatitis, diabetes mellitus types I and II, as well as pancreatic tumors, their mechanisms of inheritance and molecular biological processes are covered on the basis of scientific sources. The article considers the relationship of functional disorders in the pancreas with genetic mutations, autosomal dominant and autosomal recessive forms of inheritance, as well as the interaction between environmental factors and hereditary predisposition in the development of multifactorial diseases. Recommendations are given on early diagnosis of hereditary diseases, screening programs, preventive measures and their clinical significance.